164 Degree of Nerve Atrophy on Preoperative Imaging Predicts Outcome After Microvascular Decompression for Trigeminal Neuralgia. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Miller, Jonathan; Duan, Yifei; Sweet, Jennifer A.
Abstract: INTRODUCTION: Trigeminal neuralgia is often associated with nerve atrophy in addition to vascular compression. We sought to evaluate whether characteristics of the trigeminal nerve on preoperative imaging could be used to predict outcome after microvascular decompression. METHODS: Twenty-six consecutive patients underwent high-resolution fast-field-echo magnetic resonance imaging of the cerebellopontine angle followed by microvascular decompression for trigeminal neuralgia. Patients were divided into 2 groups based on whether they were pain-free off medications (Group A) or not (Group B) at 1 year follow-up. Preoperative images were reconstructed and reviewed by an examiner blinded to the side of symptoms and clinical outcome. For each nerve, the length of the nerve, coronal cross-sectional area at the midcisternal point, angle of the nerve with the pons and porus trigeminus, and total volume of the nerve were calculated. Student t test and Fisher exact test were used to compare the groups. RESULTS: There were 17 patients in Group A and 9 patients in Group B. Across both groups, the coronal cross-sectional area of the symptomatic trigeminal nerve was significantly smaller than on the asymptomatic side (4.3 ± 0.4 mm 2 vs 5.6 ± 0.5 mm 2, respectively; P < .05). Significantly more patients in Group B than in Group A exhibited greater than 20% decrease in cross-sectional area on the symptomatic compared with the asymptomatic side ( P < .05). There were no other differences in the radiographic appearance of the nerve between the groups. CONCLUSION: Trigeminal neuralgia is frequently associated with atrophy of the affected nerve. Greater than 20% loss of volume in the affected nerve compared with the asymptomatic side is associated with worse outcome after microvascular decompression.